Професіографічний аналіз праці машиністів електропоїздів метрополітену - Палійчук, С.П. (Актуальні проблеми транспортної медицини, 2008)
На основе изучения труда машинистов электропоездов метрополитена проведено профессиографическое исследование, позволившее определить вредные факторы производственной среды и провести соответствующее физиолого гигиеническое обоснование с целью разработки методических рекомендаций для аттестации рабочих мест за условиями труда в этой профессии. Basing on the study of work of operators of underground electric trains a professiographic study was conducted, allowing to determine factors of the work environment and to make a corresponding physiologo hygienic grounding, aiming to develop methodical recommendations for examination of work places according to work conditions in this profession.